Perfil nosológico e sociodemográfico das crianças de 0-12 anos assistidas no hospital das clínicas da Universidade Federal de Goiás no período de janeiro de 2007 a janeiro de 2010 - Araújo, Thânia Maria Claudino de Oliveira (2012)
A worlwide priority is to pay attention to child health once childhood is a singular period for the development of human being potentialities. Several factors may be associated to child health. The aim of this study was to describe the nosologic and sociodemografic profile of assisted children from birthday to 12 years old at Hospital das Clínicas (HC) of Universidade Federal de Goias (UFG), Brazil, during three years (from January-2007 to January 2010).This research is a descriptive transversal study. It was analysed 501 handbook records of 0-12 years old children, taking information about sex, age and parentage(origin) of the children, health diagnosis record in the last attendance at HC, number of attendances, kind of health service, besides data regarding the school level, functional situation and income of the parents or responsible. Descriptive and statistical analyses were presented as well. The results have revealed that most children were of the masculine sex, aged from zero to five years old, residents in Goiania and metropolitan area. This population of children was inserted in low-income families and most their fathers were self-employed and mothers were unemployed. These fathers and mothers had low school level, however, there were significantly a bigger number of mothers with the same school level than the fathers; while 27,5% of the fathers had high school level (complete or uncomplete), 41,0% of mothers had the same school level. The majority of diagnoses were respiratory system diseases while pneumonia prevailed over other ones (29,5%). The average number of attendances was 5,2 times or 1,7 health service per child, per year. The highest frequency of health service for this children s population was hospital admission. In conclusion, respiratory system diseases and in particular pneumonia remains as one of the main causes of illness and demand for children under five years to health care.